After the Wall Came Down: Academics in Post-Socialist East Germany - Dettmer, Elke (Ethnologies, 1999)
Following the reunification of 1989, in Germany joy soon gave way to disenchantment among post-socialist academics. A suddenly much more competitive environment proved a rude awakening for many who formerly had held positions with almost complete job security. Instead there has been an overwhelming tendency to replace these academies with colleagues from the West. This is a brief assessment of the situation eight years after the wall came down, based on personal observation and an eclectic choice of documentation.